Provincial Languages of Nepal and Their Endangerment - Gyanwali , Gokarna Prasad (Patan Gyansagar, 2025)
Language is essential for the ability of communities to express their cultural knowledge, and the preservation of the one is paramount to the preservation and further development of the others. There are more than 7000 languages spoken worldwide, half of which are likely to disappear within this century. In the world, 500 languages are spoken by less than 100 people, and 96% of the languages of the world are spoken by only 4% of the world’s population. Currently, out of the world's 7,168 living languages, 3,078 (43%) languages, including 114 out of 780 in India, 133 out of 320 in China, and 62 out of 124 in Nepal, are endangered (Jones, 2024). Other data say that 37 out of 131 languages ​​in Nepal (Language Commission, BS 2078) and 23 out of 124 languages ​​(National Statistics Office, BS 2078) are endangered. Almost all minority languages of Nepal and the world are in an endangered and critical state and have not become effective transmitters of culture. This paper explores the state of endangered languages and the process of their endangerment in the context of Nepal and at the provincial level. It uses primary and secondary data to describe the linguistic landscape of the country.